Effect of mixing process parameters and suitability of backbone polymer for aluminum powder injection molding feedstock - A.A. Abdullahi,; I.A. Choudhury,; M. Azuddin,; N. Nahar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A suitable and cost-effective microfabrication technique for processing aluminum micropart is required, as the choice of aluminum microparts for aerospace, electronics and automobile components is preferred over other metals due to its excellent properties. Meanwhile, powder injection molding (PIM) is identified as an economical manufacturing technique for processing ceramic and micro-metal powders into microparts and or components. Therefore, this study investigates formulation and processing of aluminum PIM feedstock using a custom-made machine. The investigation is focused on the effect of mixing process parameters (powder loading, rotor speed and mixing temperature) and the suitability of the backbone polymer. The formulated PIM feedstock constituents are paraffin wax (PW), stearic acid (SA), high-density polyethylene (HDPE)/ medium-density polyethylene (MDPE) alternatively and aluminum micro-metal powder. Taguchi method is used for the design of experiments (DOEs) and analysis. In addition, response surface methodology (RSM) is employed to develop empirical viscosity models. The optimum powder-binder mixing ratio of 58:42 vol. % with rotor speed of 43 rpm were determined for preparing aluminum PIM feedstock using mini-lab mixer developed. The empirical model developed for aluminum PIM feedstock viscosity shows a good fit with R2 values of 0.84 using HDPE and 0.96 for MDPE binder system. This investigation demonstrates preparation and suitability of aluminum PIM feedstock using wax-based binder system.